Canva Innovation in Developing Learning Media for Teachers at Muhammadiyah Takkalasi Middle School - Rika, Rika; Aslianti, Aslianti; Sangkala, Ismail; Nasir, Nasir; Hernasari, Hernasari (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2025)
Learning media is an important element in supporting the teaching and learning process. This media not only functions as a tool, but also plays a role in stimulating students' thoughts, feelings, attention and skills, so as to motivate them to learn more effectively. However, challenges in the form of teachers' lack of understanding regarding the creation of digital-based learning media often become obstacles. To overcome this problem, Educational Technology students at Muhammadiyah University of Makassar carried out training in creating learning media using the Canva application. The target of this activity is teachers from Muhammadiyah Takkalasi Middle School and Elementary School. This training aims to improve teachers' abilities in designing interesting, interactive and relevant teaching materials, so as to create a more conducive learning atmosphere and increase student motivation. Implementation methods include needs analysis, material preparation, direct training, and evaluation through discussion and distribution of questionnaires. The training stages include introducing Canva features, assistance in creating teaching materials, and evaluation sessions to overcome various obstacles experienced by participants. The results of this activity show that the teacher has succeeded in mastering the basic skills in using Canva to create more creative and innovative learning media.